Can Carbon Emissions Trading Scheme Make Power Plants Greener? Firm-Level Evidence From China - Shi, Mingxia; Zou, Tingting; Xu, Jingxuan; Wang, Jie (Frontiers in Energy Research, 2022)
The green energy structure transition is an effective means to achieve carbon emission reduction and sustainable energy development in the long term. Whether the carbon emissions trading scheme, a typical market-oriented environmental regulation, can realize green energy structure transition has attracted widespread attention. Rather than focusing on the macro-effects of the carbon emissions trading scheme, this paper explores its effect on green energy structure transition in the power sector, which is a major carbon emitter by consuming non-renewable energy. With the multi-period difference-in-differences method, this study manually collects a panel data set of 103 listed power plants from 2011 to 2020 for a total of 1030 samples and investigates the effect of carbon emissions trading scheme on the proportion of clean energy power generation. The corresponding mechanism and heterogeneous effects are also examined. The results reveal: (1) The carbon emissions trading scheme significantly improves the proportion of clean energy power generation. This improvement is achieved by increasing clean energy power generation and decreasing thermal power generation. (2) Power companies to which power plants belong are private-owned and have higher fixed asset ratios, or in regions with a high development level or strong environment law enforcement are found more responsive to carbon emissions trading schemes. (3) Green technological innovation is the main path for green energy structure transition, but it is not the only path.